BRCA1 and BRCA2 Genetic Testing in Breast and/or Ovarian Cancer Families in Iran - Fatemeh Keshavarzi; Gholam Reza Javadi; Nahid Nafissi; Mohammad Esmail Akbari; Vahid Reza Yassaee; Maryam Sharafi Farzad; Sirous Zeinali (Cell Journal, 2010)
Objective: Germline mutations in breast cancer susceptibility genes, breast cancer susceptibilitygene 1 (BRCA1) and breast cancer susceptibility gene1 (BRCA2) are responsiblefor a substantial proportion of high-risk breast and breast/ovarian cancer in families.Therefore, the aim of this study was to investigate BRCA1/2 mutations in five high riskIranian families.Materials and Methods: Of the 20 breast/ovarian cancer families counselled in our center,five were selected for BRCA1/2 mutation screening according to our minimal criteria.The complete coding sequences in addition to each intron/exon boundary of the BRCA1/2genes were screened by direct sequencing.Results: Fourteen missense substitutions were identified, which were: Gly1140Ser, Gly1738Glu,Glu1735Glu, leu871pro, Ser1613Gly, ser1040Asn, Glu1038Gly, Leu771Leuand Ser1436Ser in BRCA1; and Gln373His, Glu1391Gly, Leu1521Leu, Val2171Val andGlu1035Glu in BRCA2. In addition, the splice site mutations (IVS7+83(-TT) and so IVS8-70(-CATT) were observed in two families. Three mutations were novel (Gly1140Ser inBRCA1 and Glu1391Gly, Gln373His in BRCA2).The missense substitutions Glu1038Proand Gly1140Ser were found in a large series of patients and in five controls.Conclusion: The missense substitution Gly1738Glu in BRCA1 is pathogenic. In addition,these results showed that the probability genotype at the BRCA1 locus defined by allelesLeu871Pro, GLu1038Gly, Ser1613Gly, Gly1140Ser has an effect pathogenic. In anotherfamily sَeveral missense substitutions in BRCA1 gene such as Glu1038Gly, Gly 1140Serwere found as well as Glu1391Gly and Gln373His in BRCA2. The pathogenic effect yethas to be verified by more comprehensive populations studies.These results support this thinking that screening for BRCA1 and BRCA2 mutations mayhave the strongest impact on health-care when targeted to high-risk populations.